A new approach for some NLDEs with variable coefficients - Pandir, Yusuf; Demiray, Seyma Tuluce; Bulut, Hasan (Elsevier Gmbh, 2016)
This study is related to new soliton solutions compound KdV-Burgers equation, generalized KdV equation and (2+1) dimensional Broer-Kaup equations with variable coefficients. The generalized Kudryashov method (GKM) has been tackled for procuring exact solutions of these equations. By using this method, dark and bright soliton solutions of these equations have been found. Also, some graphical representations have been given to observe the structure of these solutions. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Compound KdV-Burgers equation; Generalized KdV equation; (2+1) dimensional Broer-Kaup equations; Generalized Kudryashov method; Dark soliton solutions and bright soliton solutions